(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
In this study, the dry powder effect of four types of Syrian marine algae Ulva fasciata , Codium tomentosum (green algae), Colpomenia sinuosa (brown algae) , and Hypnea musciformis (red algae) was studied in the growth of tobacco Plants concentrations (2, 4 and 6) grams per kilogram soil and control sample without additives, , the study was carried out in the plastic house . The comparison was done in the number of leaves, and the maximum dimensions of the leaf (length and width) in addition to flowers and fruits. The results showed the superiority of plants treated with C. tomentosum powder in the number of leaves (19 leaves) with a concentration of 2g / kg increase 4 leaves of the control sample (15 leaves) and The highest number of fruits (12 fruits), with increase 4 fruits from the control plants (8 fruits) , As well as the maximum dimensions of the leaf at the concentration 4g / Kg where the length of the leaf (25.6 cm) with increase of 4.3 cm from the maximum length of leaves of the control plants (21.3 cm) and width (15.4 cm), increase of 3.1 cm about the maximum width of the leaves of the control plants 12.3 cm) , While the number of flowers was highest in plants treated with U. fasciata powder at a concentration of 2g / Kg where it reached (30 flower) versus (25 flower) in the control plants. تم في هذا البحث اختبار تأثير المسحوق الجاف لأربعة أنواع من الطحالب البحرية السوريةUlva fasciata و tomentosum Codium (طحالب خضراء) وsinuosa Colpomenia (طحالب سمراء) و Hypnea musciformis (طحالب حمراء) في نمو نبات التبغ Tobacco من صنف شك البنت بتراكيز (2 , 4 , 6) غرام لكل كيلو غرام تربة والعينة الشاهدة دون إضافات, أجريت الدراسة في البيت البلاستيكي وتمت المقارنة من حيث عدد الأوراق والأبعاد القصوى للورقة (الطول والعرض) بالإضافة للأزهار والثمار. أظهرت النتائج تفوق النباتات المعاملة بمسحوق طحلب C. tomentosum بعدد الأوراق (19 ورقة) وذلك عند التركيز 2g/Kg بزيادة 4 أوراق عن العينة الشاهدة(15 ورقة ( كما بلغ فيها العدد الأعظمي للثمار 12) ثمرة) بزيادة 4 ثمرات عن النباتات الشاهدة (8 ثمار), وكذلك تميزت بأقصى أبعاد للورقة عند التركيز 4g/Kg حيث بلغ طول الورقة (25.6 cm) بزيادة معنوية 4.3 cm عن أقصى طول لأوراق النباتات الشاهدة(21.3 cm) وعرض (15.4 cm) بزيادة معنوية 3.1 cm عن أقصى عرض لأوراق النباتات الشاهدة (12.3 cm), في حين كان عدد الأزهار أعظمياً في النباتات المعاملة بمسحوق U. fasciata عند التركيز 2g/Kg حيث بلغ 30)زهرة) مقابل 25)زهرة) في النباتات الشاهدة.